Study on the viruses of Petunia in Hungary - Baracsi, É.; Tóth, E. K.; Kriston, E.; Takács, A.; Pribek, D.; Horváth, J. (International Journal of Horticultural Science, 2002)
Virus susceptibility of 11 varieties of vegetatively propagated petunia against 2 virus strains (TMV-C/U1 and PVYNTN) were examined. Neither resistant nor tolerant varieties of petunia were found. The virus infection of the Petunia genus was examined in Hungary. The most common pathogens were the Tobacco mosaic tobamovirus (TMV) and the Tomato mosaic tobamovirus (ToMV), but the samples also contained Alfalfa mosaic alfamovirus (AMV), Cucumber mosaic ClIC11171014171S (CMV) and Potato Y potyvirus (PVY). Potato X potexvirus (PVX) was isolated in the varieties of trailing petunia for the first time.